An Adrenal Incidentaloma: How Often Is It Detected and What Are the Consequences?. (28th November 2012) - Minnaar, E. M.; Human, K. E.; Henneman, D.; Nio, C. Y.; Bisschop, P. H.; Nieveen van Dijkum, E. J. M.
Abstract : Objectives . The aim of this study was to investigate the detection rate of adrenal incidentalomas and subsequent workup. Design . Retrospective cohort study. Methods . Two investigators evaluated the adrenals on abdominal CT scans. Abnormalities were compared to the original radiology reports and an experienced abdominal radiologist reviewed the CT scans. All additional imaging and laboratory tests were assessed. Results . The investigators detected 44/356 adrenal incidentalomas (12%). In 25 patients an adrenal incidentaloma had been noted in the radiology report. The expert radiologist agreed on 19 incidentalomas in 17 patients, two with bilateral incidentalomas. Of the 25 incidentaloma patients, 4 (16%) patients were screened for hormonal overproduction and 2 (8%) patients had follow-up imaging studies. Conclusions . 12% of the patients had an adrenal incidentaloma (42 of 356). 17 (40%) had initially not been reported by the radiologist. When diagnosed with an adrenal incidentaloma, only a small percentage of patients (16%) is screened or undergoes repeated imaging (8%) as proposed in the National Institutes of Health (NIH) guidelines on adrenal incidentalomas.